PENGARUH HARGA, LOKASI DAN INOVASI PRODUK TERHADAP KEPUTUSAN PEMBELIAN DI FOOD COURT G-TOWN SQUARE GADING SERPONG - Mahesa Zukrina Tsaqif; Shierli Wijaya (Jurnal Nusa Manajemen, 2026)
This study aims to analyze the influence of price, location, and product innovation on consumer purchase decisions at Food Court G-Town Square Gading Serpong. This research employed a quantitative approach using a survey method involving 131 respondents who were consumers of the food court. Data were analyzed using multiple linear regression to examine both simultaneous and partial effects among the research variables. The results indicate that product innovation has a significant effect on purchase decisions, while price and location do not have a significant effect. The coefficient of determination value of 0.698 shows that price, location, and product innovation simultaneously explain 69.8% of purchase decisions, while the remaining percentage is influenced by other variables outside this study. These findings suggest that product innovation is the most dominant factor in increasing purchase decisions in highly competitive food court businesses. This study is expected to provide empirical contributions to marketing management studies and serve as a strategic reference for culinary business managers in enhancing consumer attractiveness through continuous product innovation.